2008
DOI: 10.1093/her/cyn048
|View full text |Cite
|
Sign up to set email alerts
|

Can social cognitive theory constructs explain socio-economic variations in adolescent eating behaviours? A mediation analysis

Abstract: Adolescents of low socio-economic position (SEP) are less likely than those of higher SEP to consume diets in line with current dietary recommendations. The reasons for these SEP variations remain poorly understood. We investigated the mechanisms underlying socio-economic variations in adolescents' eating behaviours using a theoretically derived explanatory model. Data were obtained from a community-based sample of 2529 adolescents aged 12-15 years, from 37 secondary schools in Victoria, Australia. Adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 43 publications
12
84
1
1
Order By: Relevance
“…This finding is consistent with previous research (9) and is important since home availability of foods is an important predictor of adolescent eating behaviour (10) . It is noteworthy, however, that more than 25 % of all students reported that they usually have chocolates or soft drinks available at home.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with previous research (9) and is important since home availability of foods is an important predictor of adolescent eating behaviour (10) . It is noteworthy, however, that more than 25 % of all students reported that they usually have chocolates or soft drinks available at home.…”
Section: Resultssupporting
confidence: 92%
“…This index assesses eight dimensions of deprivation using 2006 census data, based on small-area geographical units. The index deciles were categorized into three groups reflecting low deprivation (1-3), middle levels of deprivation (4-7) and high deprivation (8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the papers reporting social patterning in the execution of different health behaviours did not formally test for the moderating effects of SES on the relationship between intention and self‐efficacy with behaviour (Ball et al ., 2007, 2009; Bere et al ., 2008; Cerin & Leslie, 2008; De Cocker et al ., 2012; Kamphuis et al ., 2008, 2009; Leganger & Kraft, 2003; Murray et al ., 2012). Furthermore, the few papers that did test for such moderating effects have been inconsistent, reporting no significant effects of moderation by SES on intention to be more physically active (Schüz et al ., 2012), or to eat more fruits and vegetables (Godin, Amireault, et al ., 2010), with Godin, Sheeran, et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the social patterning of intention to consume a healthier diet find that children and adults from higher socio‐economic groups have greater intentions to eat more healthily which was associated with consuming a healthier diet (Bere, van Lenthe, Klepp, & Brug, 2008; Leganger & Kraft, 2003; Sandvik, Gjestad, Samdal, Brug, & Klepp, 2009). Similar findings were reported for the social patterning of self‐efficacy and diet (Ball et al ., 2009). However, a study by Godin, Amireault, et al .…”
Section: Introductionmentioning
confidence: 99%